2017
DOI: 10.1002/maco.201709659
|View full text |Cite
|
Sign up to set email alerts
|

UV illumination on the atmospheric corrosion of Q450 weathering steel depositing with NH4Cl

Abstract: The studies of UV illumination and ammonium salt on the atmospheric corrosion of steel were rare. The combined effect of UV illumination and NH 4 Cl salt on the atmospheric corrosion of Q450 weathering steel was explored in this work. Mass changes results showed UV illumination distinctly accelerated the atmospheric corrosion of Q450 weathering steel depositing with NH 4 Cl. The corrosion products with semi-conductor properties could improve the corrosion current and decrease the resistance of rusted samples w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…On the one hand, the cracks formed under dark conditions provide transport channels for O 2 and H 2 O, which accelerated the cathodic reaction (Liu et al , 2019a). On the other hand, the corrosion ions in the simulated environment of the ocean atmosphere also penetrated into the matrix more easily (Sun et al , 2014; Song et al , 2018). Therefore, although UV light accelerates the corrosion rate of weathering steel, the corrosion products are denser than those under dark conditions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the one hand, the cracks formed under dark conditions provide transport channels for O 2 and H 2 O, which accelerated the cathodic reaction (Liu et al , 2019a). On the other hand, the corrosion ions in the simulated environment of the ocean atmosphere also penetrated into the matrix more easily (Sun et al , 2014; Song et al , 2018). Therefore, although UV light accelerates the corrosion rate of weathering steel, the corrosion products are denser than those under dark conditions.…”
Section: Resultsmentioning
confidence: 99%
“…As electrochemical active species, the γ -FeOOH and β -FeOOH can accelerate the corrosion process by participating in the cathodic reaction. α -FeOOH and Fe 3 O 4 were usually regarded as main compositions of protective rusts where the corrosive agents cannot reach the base metal surface (Song et al , 2018). α -FeOOH was obstructive for corrosive factors due to its insulated and inactive characteristic (Ma et al , 2008).…”
Section: Resultsmentioning
confidence: 99%
“…6,7 It has been found that ultraviolet irradiation can affect the deposition of NH 4 Cl, accelerating the anodic reaction of corrosion products with semiconductor properties, giving the material surface a larger carrier density and higher conductivity, improving the transmission ability of electrons in the rust layer, and thus accelerating the corrosion rate. 8 The corrosivity of NH 4 Cl solution is related to the acidity of the solution after hydrolysis. To reduce the rate and degree of corrosion by acid solutions, corrosion inhibitors are often injected.…”
Section: Introductionmentioning
confidence: 99%